Energy Saving of Heat Gain by Using Buried Pipe Inside a Roof - Saleh, Ahmed A. M. (Al-Khwarizmi Engineering Journal, 2014)
Abstract This work deals with a numerical investigation to evaluate the utilization of a water pipe buried inside a roof to reduce the heat gain and minimize the transmission of heat energy inside the conditioning space in summer season. The numerical results of this paper showed that the reduction in heat gain and energy saving could be occurred with specific values of parameters, like the number of pipes per square meter, the ratio of pipe diameter to the roof thickness, and the pipe inlet water temperature. Comparing with a normal roof (without pipes), the results indicated a significant reduction in energy heat gain which is about 37.8% when the number of pipes per meter of roof length is 3.0 , the ratio of pipe diameter to the wall thickness (D/W) is 0.20, and the water inlet temperature is 30°C, while the minimum ratio of reduction 24% is achieved when the number of pipes per meter, the ratio of pipe diameter to the wall thickness, and the water inlet temperature are 27, 30 and 33 °C, respectively. The results also showed that there is a very small effect of pipe centre position inside the wall on the final heat transmission. Keyword: Water pipe, Roof heat gain, Solar-air temperature.